#### Answer

$e = + \sqrt {\frac{2rE}{k}},- \sqrt {\frac{2rE}{k}} $

#### Work Step by Step

$E = \frac{e^2k}{2r}$
$2rE = e^2k$
$\frac{2rE}{k} = e^2$
$e = + \sqrt {\frac{2rE}{k}},- \sqrt {\frac{2rE}{k}} $

Published by
Pearson

ISBN 10:
013421742X

ISBN 13:
978-0-13421-742-0

$e = + \sqrt {\frac{2rE}{k}},- \sqrt {\frac{2rE}{k}} $

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.